Nucleic Acid and Protein Changes in Relation to Cold Acclimation and Freezing Injury of Korean Boxwood Leaves - Gusta, L. V. (1972)
Quantitative and qualitative differences in nucleic acids of Korean boxwood (Buxus microphylla var. Koreana) leaves were determined by methylated albumin kieselguhr chromatography at different levels of cold hardiness. During cold acclimation there was an increase in RNA, mainly ribosomal RNA, with little or no change in DNA. The increase in ribosomal RNA was closely paralleled by an increase in water soluble and membrane bound proteins. As cold hardiness increased, ribonuclease activity declined. Exposure of hardy boxwood plants to warm temperatures resulted in a rapid loss in cold resistance and a rapid synthesis of nucleic acids as judged by (32)P incorporation. Following a killing frost to Korean boxwood leaves, there was a rapid decrease in all nucleic acid fractions which was attributed to nuclease activity. Within 5 hours there was no measurable soluble RNA and ribosomal RNA. Tenaciously bound RNA was somewhat more persistent.